Interfirm relationships and trade credit in Japan : evidence from micro-data /: evidence from micro-data. ([2015]) - Uchida, Hirofumi; Ono, Arito; Kozuka, Sōichirō, 1969-; Kazama, Makoto; Uesugi, Iichiro, 1969-
No abstract available